Gangs, councillors and the apartheid state: The Newclare Squatters Movements of 1952 - Van Tonder, Deon (My University, 1989)
They were bloody clashes but ... in the context of the time and the circumstances in that part of the world, they were relatively minor. Fighting was an absolutely common feature there every weekend without exception... Periodically these became more serious... instead of one or two murders, there'd be say, half a dozen, perhaps even more. But the violence was not exceptional.. .This was the normal feature of life in Sophiatown and particularly in Newclare...Newclare was a yery tough area and like any slum ... you accept that there is violence constantly ... One must ... [also] ... remember that rioting and fighting was a form of amusement ... Young people stiff with boredom (1). This was the judgement of W.J.P. Carr, former Manager of the Non- European Affairs Department of the Johannesburg City Council, when asked about the violence in Newclare during the 1940s and 50s. Yet, in 1952, this "relatively minor" type of clash erupted into one of the largest suburbian squatter movements that Johannesburg has ever experienced. Not only did some 300 African families move across the railway line to Northern Newclare to squat on Council-owned land, but they remained there for seven months while the Johannesburg City Council and the Central Government deliberated on ways of removing them.
African Studies Seminar series. Paper presented 23 October 1989. Not to be quoted without the Author's permission.
Keywords: Slums. South Africa; South Africa. Ethnic relations; Johannesburg (South Africa). Ethnic relations